CRYPTOMICSDB: Revealing the Molecular Landscape of Cryptococcosis - Yohana Porto Calegari-Alves; Camila Innocente-Alves; Renata Pereira Costa; Aline Martins Faustino; Karyn Scheffler Schirma Farias; Mateus Boiani; Bruno Samuel Ardenghi Gonçalves; Marcio Dorn; Walter Orlando Beys-da-Silva; Lucélia Santi (Journal of Fungi)
Cryptococcosis is a serious fungal infection mainly caused by two Cryptococcus species, Cryptococcus gattii and Cryptococcus neoformans species complexes. Even though it is considered a dangerous disease, this infection is also neglected worldwide and its research is not adequately funded. The molecular understanding of the infection, which could help in the development of specific treatments and appropriate management, is hampered, as molecular data are not of easy access. With that purpose, our group developed a Cryptococcus molecular database, grouping published molecular data on gene and protein differential expression that occurred due to the infection. CRYPTOMICSDB presents a user-friendly interface, and users can search for both pathogen or host information and visualize data on experimental approaches, animal models or cell culture, Cryptococcus species and strain, genes and proteins. The database features 19,462 and 986,507 total genes related to the pathogen and host views, respectively. CRYPTOMICSDB is a powerful tool that can help health workers and microbiology researchers to better understand the molecular impact caused by cryptococcosis infection process.